Nutrition characteristics and delivery in relation to 28-day mortality in mechanically-ventilated patients admitted to a government hospital in the Maldives - Abdul Raheem, Asiya (2021)
Maldives and other South Asian countries are lacking on data regarding nutrition characteristics and delivery of critically ill patients. Mortality rate of mechanicallyventilated patients in South Asian countries is not much researched. Involvement of dietitian in managing critically ill patients is not very well mentioned. Besides, nutritional characteristics and delivery of critically ill patients is not very well established. The purpose of this prospective observational study was to investigate nutrition characteristics and delivery, and its association with 28-day mortality of mechanically-ventilated patients admitted to intensive care units of a tertiary-care hospital of the Maldives. Data of the mechanically-ventilated patients were collected using universal sampling method from patient charts in the ICU using a self-developed questionnaire. Disease severity was assessed using APACHE II score and SOFA score. Nutritional screening was done using mNUTRIC score. Energy and protein were calculated from commercial feeds, blended tube feeds and parenteral nutrition based on manufacturers instruction on energy and protein content in the products. Each patient was followed for a maximum of 28 days. From the total of 115 recruited in the study, 53% died within 28 days of admission in ICU. Patient characteristics, nutrition characteristics and nutrition delivery were not associated with 28-day mortality. In the unadjusted logistic regression analysis, intervention by dietitian (OR = 0.250, 95% CI: 0.066 – 0.940, p = 0.040) significantly contributed to 28-day mortality. After adjusting to sex, length of stay in ICU, SOFA score and mNUTRIC score, intervention by dietitian no longer contributed to 28-day mortality (OR = 0.338, 95% CI: 0.081 – 1.417, p = 0.138). 28-day mortality was much higher in this study than that of similar studies. Although none of the nutritional characteristics and delivery were related to mortality, patients receiving intervention by dietitian had lesser chance of death within 28 days of ICU admission.